2020
DOI: 10.1159/000505753
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Intravitreal Injection of Conbercept as an Initial Treatment for Exudative Circumscribed Choroidal Hemangioma

Abstract: Objective: To investigate the effectiveness and safety of intravitreal injection of conbercept (IVC) as the initial treatment for exudative circumscribed choroidal hemangioma (CCH). Methods: Forty-two eyes of 42 patients received 3 monthly IVC (0.5 mg/0.05 mL) as the initial treatment. Three months later, the patients were assessed for further treatment including observation, reinjection of conbercept, laser photocoagulation (if the lesion was 3,000 μm away from the macular fovea), or photodynamic therapy (PDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…VEGF-A is an important pro-angiogenic factor associated with angiogenesis in tumors and retinal vascular disease. Anti- (11,12). Although anti-VEGF therapy has been proved effective in treating CCH with exudative retinal detachment, the current study is the first report which actually shows the elevation of VEGF-A in aqueous humor of from patients with CCH.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…VEGF-A is an important pro-angiogenic factor associated with angiogenesis in tumors and retinal vascular disease. Anti- (11,12). Although anti-VEGF therapy has been proved effective in treating CCH with exudative retinal detachment, the current study is the first report which actually shows the elevation of VEGF-A in aqueous humor of from patients with CCH.…”
Section: Discussionmentioning
confidence: 61%
“…Since then, Mandal et al has documented the complete resolution of leakage after intravitreal bevacizumab in 3 cases of CCH patients and Lai et al. showed that using intravitreal conbercept as primary treatment for exudative CCH was effective in maintaining BCVA and decreasing the central foveal thickness ( 11 , 12 ). Although anti-VEGF therapy has been proved effective in treating CCH with exudative retinal detachment, the current study is the first report which actually shows the elevation of VEGF-A in aqueous humor of from patients with CCH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation